Drug problem or medicrime? Distribution and use of falsified Tramadol medication in Egypt and West Africa - Klein, Axel (Journal of illicit economies and development, 2019)
Tramadol is a synthetic opioid that is widely used as an analgesic for alleviating pain of moderate to medium intensity. With potency estimated to be about one-tenth that of morphine, tramadol is considered as relatively safe with regard to poisonings or dependency. Yet there are increasing reports of widespread non-medical consumption of tramadol in North and West Africa. The Egyptian government has requested the UN Commission of Narcotic Drugs to put tramadol under international control. This will have profound implications for the treatment of acute and chronic pain across developing countries where tramadol is often the only available analgesic, because controlled substances are impossible to obtain for health care practitioners. The tramadol sold outside of medical establishments is often adulterated and substandard, part of the massive trade in falsified medicines that is possibly far more devastating than the hedonic use of psychoactive substances. Yet the international machinery in place to control medical products is feeble and the penalties for medicrime are modest next to drug trafficking offences. The article suggests that international controls need to re-assess their priorities to focus on human and patient well-being. A further shift is needed away from repressive measures against consumers, to tighter regulation in the production and distribution of medications and pharmaceutical substances. This must involve a wide range of stakeholders, including health care practitioners, the pharmaceutical industry, pharmacists, patients associations, and the public at large.